2015
DOI: 10.1177/1071100715603983
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play in National Football League Players After Operative Jones Fracture Treatment

Abstract: Background: Jones fractures commonly occur in professional athletes and operative treatment remains the standard of care in this patient population. In our clinical experience, an aggressive postoperative rehabilitation protocol for National Football League (NFL) players with an average return to play (RTP) between 8 and 10 weeks can have successful outcomes with few complications. The purpose of this study was to quantify RTP and rate of complications, including nonunion, refracture, and reoperation among a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(137 citation statements)
references
References 34 publications
(52 reference statements)
5
132
0
Order By: Relevance
“…Surgical preparation of the intramedullary canal was carried out according to the manufacturer's proposed technique. A 2.0 mm guide wire was inserted “high and inside” by direct visualization and orientation, inspired by previously published anatomical landmarks . Afterward a 3.5 mm drill guide was introduced over the guide wire and a 3.5 mm cannulated drill was advanced into the proximal aspect of the fifth metatarsal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgical preparation of the intramedullary canal was carried out according to the manufacturer's proposed technique. A 2.0 mm guide wire was inserted “high and inside” by direct visualization and orientation, inspired by previously published anatomical landmarks . Afterward a 3.5 mm drill guide was introduced over the guide wire and a 3.5 mm cannulated drill was advanced into the proximal aspect of the fifth metatarsal.…”
Section: Methodsmentioning
confidence: 99%
“…During taping the appropriate screw size and length was measured. The required screw length was estimated as about 70% of the metatarsal length and selected by visual inspection superimposing the screw over the metatarsal . Care was taken that the screw was not too long, preventing lateral fracture site gapping, but long enough that threads were distal to the fracture site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DeLee et al (1983) and Raikin and colleagues (2008) both found a relationship between proximal fifth metatarsal fractures and hindfoot varus deformity, implicating excess lateral column loading as a possible etiology (3,5). Similarly, certain sports (e.g., basketball and football) which involve large amounts of pivoting may also be associated with an increased risk for developing Jones fractures (6,7). This is thought to be due to the excess stress placed on the lateral side of the forefoot while the ankle is somewhat plantar flexed during pivoting maneuvers (5,8).…”
Section: Introductionmentioning
confidence: 99%